Identification of indigenous bacteria isolated from shrimp aquaculture wastewater with bioremediation application: total ammoniacal nitrogen (TAN) and nitrite removal - Sarmila Muthukrishnan,; Vikineswary Sabaratnam,; Geok-Yuan, Annie Tan; Ving, Ching Chong (Universiti Kebangsaan Malaysia, 2015)
Deterioration of water quality mainly due to high total ammonia nitrogen (TAN) and nitrite will affect the productivity of shrimp culture. In this study, three indigenous strains assigned as VCM5, VCM8 and VCM12 were evaluated for their ability to degrade TAN and nitrite. These strains were inoculated into shrimp aquaculture wastewater to enhance the degradation of TAN and nitrite. All the strains reduced TAN and nitrite level from the shrimp aquaculture wastewater significantly (p<0.05). Strain VCM5 (GenBank accession number KJ700465) and VCM8 (GenBank accession number KJ700464) showed 99.71% sequence similarity with the 16S rRNA gene type species Bacillus vietnamensis 15-1T (ABO99708) and strain VCM12 (GenBank accession number KJ700463) showed 99.05% sequence similarity with 16S rRNA gene sequence type species Gordonia bronchialis DSM43247T (CP001802).